Four Cities : a Study in Comparative Policy Making - Williams, Oliver P.; Adrian, Charles R. (Philadelphia, Pa. : University of Pennsylvania Press, 2016)
This is an analysis of the political process in four middle-sized unnamed American cities between the years 1948 and 1957.
Frontmatter -- Preface -- Contents -- Part I. Introduction -- Chapter I. The Study Approach -- Chapter II. The Four Cities -- Part II. The Political Process -- Chapter III. Nonpartisanship: The Recruitment of Elective Officials -- Chapter IV. Nonpartisanship: Electoral Patterns -- Chapter V. Referendums -- Chapter VI. The Main-Street Merchants -- Chapter VII. The Local Interests of Labor -- Chapter VIII. The Neighborhoods -- Part III. A Typology of Civic Policies -- Chapter IX. Type One: Promoting Economic Growth -- Chapter [. Type Two: Providing Life's Amenities -- Chapter XI. Type Three: Maintenance of Traditional Services -- Chapter XII. Type Four: Arbitration Among Conflicting Interests -- Part IV. Conclusions -- Chapter XIII. Community Differences and Policy Variations -- Chapter XIV. Political Institutions and the Structure of Politics -- Appendixes -- Index
In English.
Online resource; title from PDF title page (publisher's Web site, viewed Dec. 09, 2016).
JSTOR
Keywords: Municipal government -- United States -- Case studies; Administration municipale -- États-Unis -- Études de cas; POLITICAL SCIENCE -- Public Policy -- City Planning & Urban Development; Municipal government; United States; Case studies